Relationship between maturity index and ethylene production patterns of 'Williams' pears grown in the Alto Valle of Río Negro - Gomila, Teofilo; Calvo, Gabriela; Candan, Ana Paula (ISHS, 2025)
Trabajo presentado al XI International Pear Symposium, Argentina, 2010